O luto e as esferas do sofrimento na pandemia de 2020 - Oliveira, Mayra de Fátima Martins de (Universidade Federal de São Carlos, 2020)
The final paper of medical school at the Federal University of São Carlos proposes to be a critical-reflexive narrative that synthesizes experiences lived during graduation regarding learning and medical care. Using knowledge acquired in the activities of the Academic League of Antalgic Therapy and Palliative Care (LATACP-UFSCar) - on grief, communicating bad news, suffering and total pain -, this work seeks to reflect on the challenges faced during the pandemic of COVID-19 in the Brazilian context of political, social and environmental crisis, as well as perspectives for the future and strategies of self-care in this uncertain scenario.
The grieving and the spheres of suffering in the 2020 pandemic
Keywords: Luto; Sofrimento; Pandemia COVID-19 no Brasil; Grieving; Suffering; COVID-19 pandemic in Brazil; CIENCIAS DA SAUDE::SAUDE COLETIVA::MEDICINA PREVENTIVA